Afghanistan’s Crucial Shift: From Semi - Liberal Democracy to Islamic Emirate and Its Implications - Shakib, Ahmad Javid (Integrated Journal for Research in Arts and Humanities, 2025)
This article examines Afghanistan's profound political shift from a Western-backed semi liberal democracy to the reestablishment of the Islamic Emirate under the Taliban. It explores the historical context of regime changes, highlighting ideological conflicts between religious conservatism and secular liberalism since the 20th century. The study analyzes the implications of this transition for Afghanistan's socio-political landscape and its international relations, focusing on the Taliban's implementation of policies that challenge both national and international norms. Through fieldwork, including interviews with Taliban members, scholars, and ordinary citizens, the author provides insights into the domestic policies of the Islamic Emirate and the responses from various Afghan demographics. The article concludes with reflections on the future governance of Afghanistan and the challenges posed by a young, urbanized population that has been shaped by two decades of liberal democracy.